CLUSTER APPROACH IN THE STATE POLICY OF SMALL BUSINESS DEVELOPMENT MANAGEMENT IN THE REGIONS - SHPILEVA, Vira; CHEREVKO Оlexandr (Herald of Khmelnytskyi National University. Economic sciences, 2022)
The article substantiates the scientific substantiation of the theoretical and methodological features of the cluster approach in the state policy of small business development management, taking into account a set of progressive requirements for the organization of entrepreneurial activity. The substantive essence of the small business sphere and its role in ensuring the stability of the country’s economy are described. The distinctive features of small business are mobility and maneuverability in a competitive environment, efficiency in terms of economic and investment costs, and all this allows to ensure a high return on investment, the ability to respond quickly to changes in investment, increasing investment activity. The importance of joint solution of economic problems in achieving the required level of growth, which should be embedded in the development and implementation of state policy for small business management. Targets for the introduction of a cluster approach and its importance in the system of establishing state support for small business development are revealed. The cluster approach identifies a set of elements that justify the targets of both small businesses and all stakeholders in this type of association. The importance of forming common functional directions of cluster participants development and building an effective system of public administration, which provides for the creation of favorable conditions for the implementation of such an approach in the field of small business. Functional directions of introduction of cluster approach in the system of state management of small business development concerning modernization of business activity, regulation of the environment of functioning, increase of a set of competitive advantages, maintenance of realization of social and economic interests are formed. The peculiarities of the state policy of small business development management, which were established in the context of the introduction of the cluster approach, are determined. It is proposed to consider the cluster as an institution that, by combining the resource capabilities of the participants, is able to form all possible tools to solve the problems of each of them. Such an association must first of all have an established institutional and legal plane, be supported by market participants, and meet the progressive standards of the international economy.